Impermeable shotcrete applied to limestone region and preparation method of impervious shotcrete

By designing a anti-seepage spray concrete containing polypropylene fibers, cellulose fibers and anti-seepage enhancers in the limestone area, the crystal blockage problem caused by groundwater permeability and cement hydration process of tunnel drainage system is solved, and high efficiency is achieved anti-seepage properties and structural safety.

CN119490332APending Publication Date: 2025-02-21GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311041193.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In limestone areas, the tunnel drainage system is prone to crystallization blockage due to groundwater permeability and cement hydration process, affecting the durability and construction progress of the tunnel structure.

Method used

A kind of anti-permeable jet concrete is designed, and its mix includes ordinary silicate cement, fly ash, silica fume, fine aggregate, coarse aggregate, water, polypropylene fiber, cellulose fiber and anti-permeable reinforcement, through The combination of these components enhances the concrete's seepage resistance.

Benefits of technology

The average compressive strength and tensile strength of the anti-seepage concrete were significantly improved in 7 days and 28 days. It has low porosity and high density. It can effectively resist groundwater erosion and prevent crystallization of support jet concrete in the early stage of the tunnel. Problem: Ensure the safety of the tunnel structure and the smooth flow of the drainage system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490332A_ABST
    Figure CN119490332A_ABST
Patent Text Reader

Abstract

The invention discloses impermeable sprayed concrete applied to limestone areas and a preparation method thereof, and belongs to the field of tunnel construction. The impervious shotcrete applied to the limestone area can effectively prevent the seepage crystallization problem of the shotcrete for the primary support of a tunnel. The impermeable shotcrete applied to the limestone area has a good seepage and crystallization prevention effect in the early stage, more calcium fixing agents can play a role in the follow-up seepage process, the shotcrete is more compact, the purpose of resisting long-term seepage crystallization is achieved, and the impermeable shotcrete can be applied to water-rich tunnels, especially water-rich tunnels with corrosive underground water. The problem of seepage crystallization of tunnel primary support sprayed concrete can be effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, and in particular to an anti-seepage shotcrete used in limestone areas and a preparation method thereof. Background Art

[0002] The tunnel drainage system refers to the waterproofing and drainage project carried out to maintain the tunnel construction from water leakage, threatening the safety of pedestrians, eroding the facilities in the tunnel, and affecting the designed service life. It is a comprehensive project including geology, meteorology, construction strata and hydrology, construction methods, construction technology and material performance. The drainage system guides the interstitial water and surface water from the outside of the lining to the drainage well to reduce the water pressure in the tunnel to ensure the safety of the tunnel structure. In order to ensure the safety of the tunnel structure, the normal operation of the drainage system is crucial. During the construction of the tunnel and after the completion of the construction, the tunnel interstitial water must be guided and combed in time. During the drainage of the drainage system, the water body is in close contact with the air, the pH and CO2 content of the interstitial water increase rapidly, and crystals begin to accumulate on the pipe wall. As time goes by, the accumulation effect becomes more significant, and the interception phenomenon gradually occurs, so that the water pipe is completely blocked, affecting the normal operation of the drainage operation. Among many tunnels, the crystallization of pipes in limestone areas is the most serious. Often, a large number of crystals appear during the construction of the tunnel, causing the tunnel drainage system to fail to operate normally, requiring manual drainage and dredging, which seriously affects the construction progress and may bring secondary disasters such as tunnel water inrush and landslides.

[0003] At present, composite lining is commonly used in highway tunnels, that is, primary support + secondary lining. However, composite lining also leads to certain problems, especially for primary support and tunnel drainage system in limestone areas. Groundwater seeps in the primary support concrete for a long time. Shotcrete is eroded by various corrosive groundwater due to calcium dissolution. Groundwater easily penetrates shotcrete and invades the tunnel, affecting the durability of tunnel structure and construction progress. In shotcrete, gel material is continuously hydrated to generate hydration products such as calcium hydroxide and hydrated calcium silicate. When groundwater rich in corrosive ions continuously passes through the concrete, cement hydration products are dissolved and carried out, and flow into the tunnel drainage system with the corrosive liquid, thereby accelerating the crystallization blockage of the drainage system. Once the drainage system is blocked, the groundwater behind the lining cannot be discharged in time, and then acts on the outside of the support structure and the bottom of the road surface in the form of pressure, causing the lining and the road surface to bear additional additional water pressure, resulting in a large number of tunnels. Shortly after the construction, the lining cracks, water leakage and road surface water gushing appeared, seriously endangering the safety of tunnel operation. Summary of the invention

[0004] In order to solve the problems in the prior art, the present invention provides an anti-seepage shotcrete for limestone areas and a preparation method thereof. Based on the characteristics that tunnel crystallization disease is closely related to the permeability of shotcrete and the cement hydration process, the present invention enhances its anti-seepage performance by designing the mix ratio of anti-seepage shotcrete, and plays a preventive and therapeutic role on tunnel crystallization disease.

[0005] Specifically, the present invention is applied to anti-seepage shotcrete in limestone areas, and is composed of the following raw materials in parts by weight: 297 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.5 parts of polypropylene fiber, 1.2 parts of cellulose fiber, and 10-40 parts of anti-seepage enhancer.

[0006] Preferably, the fly ash is primary fly ash.

[0007] Preferably, the fine aggregate is river sand with a particle size distribution of 0 to 2 mm.

[0008] Preferably, the coarse aggregate is crushed stone with a particle size of 5 to 8 mm.

[0009] Preferably, the high efficiency water reducer is a powdered polycarboxylate water reducer.

[0010] Preferably, the density of the polypropylene fiber is 0.91 g / cm 3 , melting point 165-175℃, ignition point 590℃, length 12-24mm, diameter 20-30μm, aspect ratio>500, elongation at break 2-3%, tensile strength>2800MPa. Breaking strength ≥300MPa, elastic modulus ≥2500MPa, Poisson's ratio 0.29-0.46.

[0011] Polypropylene fiber is a synthetic fiber spun from isotactic polypropylene obtained by propylene polymerization. It has the advantages of low density, good heat resistance, high strength, good toughness, good alkali resistance, high elongation and low price. When polypropylene fiber is added to cement base material, the crack resistance will be increased by more than 1.2 times. Under reasonable proportion and construction standard, it can completely prevent the appearance of cracks. When added to concrete or mortar, it can effectively control the cracks caused by plastic shrinkage cracking or temperature changes in concrete or mortar, prevent and inhibit the growth of cracks, thereby improving the anti-seepage and anti-cracking properties of concrete. Adding polypropylene fiber can also greatly improve the crack resistance and impact resistance of concrete or mortar, resist wear and freeze-thaw, and reduce plastic settlement and cracking.

[0012] Preferably, the cellulose fiber is 1.10 g / cm 3 , length 6mm, diameter 15-20μm, breaking strength ≥700MPa.

[0013] Cellulose fibers contain unique cavities, which can slowly release the water stored in the cavities during the hardening process of concrete, promote further hydration of concrete, and compensate for concrete shrinkage. Cellulose fibers have the following advantages: natural hydrophilicity, which can provide water for cement hydration, make the hydration products adhere to its surface, and improve the bonding strength between the fiber and the cement matrix; generally in the form of flakes, it is very easy to randomly disperse and not agglomerate during the preparation of concrete, so that it is evenly distributed in the concrete to form a three-dimensional network structure; large number per unit mass, small spacing, and large specific surface area can effectively inhibit the initiation and development of cracks in the early stage of concrete hardening and improve strength; high strength, high modulus, and strong bond strength have a positive effect on improving the toughness, impact resistance, and durability of concrete in the later stage, such as impermeability, frost resistance, carbonization resistance, and erosion resistance.

[0014] Preferably, the anti-seepage enhancer is prepared by the following method:

[0015] 1) ball-milling 2040 parts of lithium carbonate, 1530 parts of aluminum hydroxide, 1020 parts of aluminum silicate powder, 5-10 parts of nano silicon dioxide and 5-10 parts of nano calcium carbonate by weight to obtain a mixed powder;

[0016] 2) soaking the mixed powder in anhydrous ethanol, adding stearic acid, methacrylic acid or aminosulfonic acid,

[0017] Heating to 40-60° C., and then stirring at a rotation speed of 100 r / min for 30-90 min to obtain a coated mixture;

[0018] 3) Drying the coated mixed material to obtain coated structure polymer powder.

[0019] Furthermore, in step 1), the particle size of the aluminum hydroxide is 0.5 to 2 μm; the particle size of the aluminum silicate powder is 200 to 300 μm;

[0020] In step 1), the particle size of the nano-silicon dioxide is 1520nm and the specific surface area is ≥150m 2 / g.

[0021] Furthermore, in step 1), the average particle size of the nano calcium carbonate is ≤100 nm, the whiteness is >93%, and the specific surface area is ≥20 m 2 / g.

[0022] Furthermore, the total mass of stearic acid, methacrylic acid and / or aminosulfonic acid added in step 2) is 3% to 5% of the mass of the mixed powder.

[0023] Further, the ball milling in step 1) is specifically as follows:

[0024] The raw materials are dispersed and mixed at high speed and then added into a ball mill, and then Al2O3 grinding balls are added, and the raw materials are ball milled at a speed of 300-400 r / min for 2-4 hours, and then sieved through a 200-mesh sieve to obtain a mixed powder.

[0025] Furthermore, the mass ratio of Al2O3 grinding balls to mixed powder is (10-15):1.

[0026] Further, the drying method of step 3) is:

[0027] Dry in a rotary evaporator for 3 to 5 hours.

[0028] The present invention also relates to a method for preparing the above-mentioned impermeable shotcrete, which specifically comprises the following steps:

[0029] 1) First, add the ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate, high-efficiency water reducer and anti-seepage enhancer weighed by weight into a mixer and stir slowly to mix the dry materials evenly;

[0030] 2) Then add water to the blender and stir slowly;

[0031] 3) Slowly add the polypropylene fiber and the cellulose fiber into the mixer and stir quickly to disperse the fibers evenly and avoid agglomeration;

[0032] 4) Pour the stirred slurry into a mold, vibrate it into shape, and seal it with a plastic film. After demoulding, continue to cure it at room temperature for 28 days.

[0033] Preferably, the slow stirring time in step 1) is 5 min.

[0034] Preferably, the slow stirring time in step 2) is 3 minutes.

[0035] Preferably, the rapid stirring time in step 3) is 5 min.

[0036] Preferably, the vibration time in step 4) is 2 min.

[0037] Preferably, the rotation speed of slow stirring is 100-125 r / min, and the rotation speed of fast stirring is 195-230 r / min.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The anti-seepage shotcrete of the present invention is applied to limestone areas and can effectively prevent the seepage crystallization problem of shotcrete in the initial support of tunnels.

[0040] The anti-seepage shotcrete of the present invention is applied to limestone areas. The shotcrete mixed with polypropylene fiber, cellulose fiber and anti-seepage enhancer has an average compressive strength of 38.57MPa at 7 days, an average compressive strength of 53.70MPa at 28 days, an average tensile strength of 2.70MPa at 7 days, an average tensile strength of 3.54MPa at 28 days, and a bonding strength with surrounding rocks of more than 3.20MPa. The shotcrete mixed with polypropylene fiber, cellulose fiber and anti-seepage enhancer has the characteristics of low porosity and high density, good anti-seepage performance, good resistance to groundwater erosion of lining, and provides a rich safety reserve for safe operation of tunnels. The anti-seepage shotcrete of the present invention applied to limestone areas not only has a good seepage and anti-crystallization effect in the early stage, but also the subsequent seepage process will make more anti-seepage enhancers play a role, and the shotcrete is more dense, which can resist the purpose of long-term seepage crystallization. For water-rich tunnels in limestone areas, especially water-rich tunnels with corrosive groundwater, it can effectively prevent the seepage crystallization problem of shotcrete in the initial support of the tunnel, and further ensure the safety of the tunnel structure and the smooth operation of the drainage system. Compared with ordinary concrete, the concrete of the present invention has good construction performance, fast spraying speed, and small rebound. Compared with ordinary concrete, the shotcrete of the present invention can save 1 / 3 of the spraying time. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a technical flow chart of the present invention.

[0042] Figure 2 The present invention is a flow chart of the technical solution for the preparation of anti-seepage enhancers.

[0043] Figure 3 This is an electron microscope scanning image of the concrete after 120 days of seepage in Example 4 DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings:

[0045] In order to further illustrate the present invention, the following detailed description is given of an anti-seepage shotcrete for limestone areas and a preparation method provided by the present invention in combination with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0046] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.

[0047] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.

[0048] Example 1

[0049] The raw materials prepared in Example 1 are in the following proportions by mass: 297 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.5 parts of polypropylene fiber, 1.2 parts of cellulose fiber, and 10 parts of anti-seepage enhancer.

[0050] In parts by weight, 20-40 parts of lithium carbonate, 15-30 parts of aluminum hydroxide with a particle size of 0.5-2 μm, 10-20 parts of aluminum silicate powder with a particle size of 200-300 μm, and 5-10 parts of a powder with a particle size of 1520 nm and a specific surface area of ​​≥150 m 2 / g of nano silicon dioxide and 5-10 parts of average particle size ≤100nm, whiteness>93%, specific surface area ≥20m 2 / g of nano calcium carbonate powder is mixed and added into a ball mill, and then Al2O3 grinding balls are added according to the principle that the mass ratio of Al2O3 grinding balls to mixed powder is (10-15):1, and ball milling is carried out at a rotation speed of 300-400r / min for 2-4h, and then sifted through a 200-mesh sieve to obtain a mixed powder; the mixed powder is immersed in anhydrous ethanol, and stearic acid, methacrylic acid or aminosulfonic acid with a total mass of 3%-5% of the mass of the mixed powder is added, and the mixture is heated to 40-60°C, and then stirred at a rotation speed of 100r / min for 30-90min to obtain a coated mixed material; the coated mixed material is placed in a rotary evaporator for drying for 3-5h to obtain a coated structure polymer powder, i.e., an anti-seepage enhancer.

[0051] After obtaining the anti-seepage enhancer, add ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate, high-efficiency water reducer and anti-seepage enhancer weighed by weight into a mixer and slowly stir at a speed of 100-125r / min for 5 minutes to mix the dry materials evenly; then add water to the mixer and slowly stir at a speed of 100-125r / min for 3 minutes; then slowly add polypropylene fiber and cellulose fiber into the mixer and quickly stir at a speed of 195-230r / min for 5 minutes to evenly disperse the fibers and avoid agglomeration; pour the stirred slurry into a mold, vibrate for 2 minutes, seal with a plastic film after molding, and continue to cure at room temperature for up to 28 days after demolding.

[0052] Example 2

[0053] The mass proportions of raw materials prepared in Example 2 are: 287 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.5 parts of polypropylene fiber, 1.2 parts of cellulose fiber, and 20 parts of anti-seepage enhancer.

[0054] In parts by weight, 20-40 parts of lithium carbonate, 15-30 parts of aluminum hydroxide with a particle size of 0.5-2 μm, 10-20 parts of aluminum silicate powder with a particle size of 200-300 μm, and 5-10 parts of a powder with a particle size of 1520 nm and a specific surface area of ​​≥150 m 2 / g of nano silicon dioxide and 5-10 parts of average particle size ≤100nm, whiteness>93%, specific surface area ≥20m 2 / g of nano calcium carbonate powder is mixed and added into a ball mill, and then Al2O3 grinding balls are added according to the principle that the mass ratio of Al2O3 grinding balls to mixed powder is (10-15):1, and ball milling is carried out at a rotation speed of 300-400r / min for 2-4h, and then sifted through a 200-mesh sieve to obtain a mixed powder; the mixed powder is immersed in anhydrous ethanol, and stearic acid, methacrylic acid or aminosulfonic acid with a total mass of 3%-5% of the mass of the mixed powder is added, and the mixture is heated to 40-60°C, and then stirred at a rotation speed of 100r / min for 30-90min to obtain a coated mixed material; the coated mixed material is placed in a rotary evaporator for drying for 3-5h to obtain a coated structure polymer powder, i.e., an anti-seepage enhancer.

[0055] After obtaining the anti-seepage enhancer, add ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate, high-efficiency water reducer and anti-seepage enhancer weighed by weight into a mixer and slowly stir at a speed of 100-125r / min for 5 minutes to mix the dry materials evenly; then add water to the mixer and slowly stir at a speed of 100-125r / min for 3 minutes; then slowly add polypropylene fiber and cellulose fiber into the mixer and quickly stir at a speed of 195-230r / min for 5 minutes to evenly disperse the fibers and avoid agglomeration; pour the stirred slurry into a mold, vibrate for 2 minutes, seal with a plastic film after molding, and continue to cure at room temperature for up to 28 days after demolding.

[0056] Example 3

[0057] The mass proportions of raw materials prepared in Example 3 are: 277 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.5 parts of polypropylene fiber, 1.2 parts of cellulose fiber, and 30 parts of anti-seepage enhancer.

[0058] In parts by weight, 20-40 parts of lithium carbonate, 15-30 parts of aluminum hydroxide with a particle size of 0.5-2 μm, 10-20 parts of aluminum silicate powder with a particle size of 200-300 μm, and 5-10 parts of a powder with a particle size of 1520 nm and a specific surface area of ​​≥150 m 2 / g of nano silicon dioxide and 5-10 parts of average particle size ≤100nm, whiteness>93%, specific surface area ≥20m 2 / g of nano calcium carbonate powder is mixed and added into a ball mill, and then Al2O3 grinding balls are added according to the principle that the mass ratio of Al2O3 grinding balls to mixed powder is (10-15):1, and ball milling is carried out at a rotation speed of 300-400r / min for 2-4h, and then sifted through a 200-mesh sieve to obtain a mixed powder; the mixed powder is immersed in anhydrous ethanol, and stearic acid, methacrylic acid or aminosulfonic acid with a total mass of 3%-5% of the mass of the mixed powder is added, and the mixture is heated to 40-60°C, and then stirred at a rotation speed of 100r / min for 30-90min to obtain a coated mixed material; the coated mixed material is placed in a rotary evaporator for drying for 3-5h to obtain a coated structure polymer powder, i.e., an anti-seepage enhancer.

[0059] After obtaining the anti-seepage enhancer, add ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate, high-efficiency water reducer and anti-seepage enhancer weighed by weight into a mixer and slowly stir at a speed of 100-125r / min for 5 minutes to mix the dry materials evenly; then add water to the mixer and slowly stir at a speed of 100-125r / min for 3 minutes; then slowly add polypropylene fiber and cellulose fiber into the mixer and quickly stir at a speed of 195-230r / min for 5 minutes to evenly disperse the fibers and avoid agglomeration; pour the stirred slurry into a mold, vibrate for 2 minutes, seal with a plastic film after molding, and continue to cure at room temperature for up to 28 days after demolding.

[0060] Example 4

[0061] The mass proportions of raw materials prepared in Example 4 are: 267 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.5 parts of polypropylene fiber, 1.2 parts of cellulose fiber, and 40 parts of anti-seepage enhancer.

[0062] In parts by weight, 20-40 parts of lithium carbonate, 15-30 parts of aluminum hydroxide with a particle size of 0.5-2 μm, 10-20 parts of aluminum silicate powder with a particle size of 200-300 μm, and 5-10 parts of a powder with a particle size of 1520 nm and a specific surface area of ​​≥150 m 2 / g of nano silicon dioxide and 5-10 parts of average particle size ≤100nm, whiteness>93%, specific surface area ≥20m 2 / g of nano calcium carbonate powder is mixed and added into a ball mill, and then Al2O3 grinding balls are added according to the principle that the mass ratio of Al2O3 grinding balls to mixed powder is (10-15):1, and ball milling is carried out at a rotation speed of 300-400r / min for 2-4h, and then sifted through a 200-mesh sieve to obtain a mixed powder; the mixed powder is immersed in anhydrous ethanol, and stearic acid, methacrylic acid or aminosulfonic acid with a total mass of 3%-5% of the mass of the mixed powder is added, and the mixture is heated to 40-60°C, and then stirred at a rotation speed of 100r / min for 30-90min to obtain a coated mixed material; the coated mixed material is placed in a rotary evaporator for drying for 3-5h to obtain a coated structure polymer powder, i.e., an anti-seepage enhancer.

[0063] After obtaining the anti-seepage enhancer, add ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate, high-efficiency water reducer and anti-seepage enhancer weighed by weight into a mixer and slowly stir at a speed of 100-125r / min for 5 minutes to mix the dry materials evenly; then add water to the mixer and slowly stir at a speed of 100-125r / min for 3 minutes; then slowly add polypropylene fiber and cellulose fiber into the mixer and quickly stir at a speed of 195-230r / min for 5 minutes to evenly disperse the fibers and avoid agglomeration; pour the stirred slurry into a mold, vibrate for 2 minutes, seal with a plastic film after molding, and continue to cure at room temperature for up to 28 days after demolding.

[0064] Comparative Example 1

[0065] The mass proportions of raw materials prepared in Comparative Example 1 are: 297 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, and 7.3 parts of high-efficiency water reducing agent.

[0066] Add ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate and high-efficiency water reducing agent weighed by weight into a mixer and slowly stir at a speed of 100-125r / min for 5 minutes to mix the dry materials evenly; then add water to the mixer and slowly stir at a speed of 100-125r / min for 3 minutes; pour the stirred slurry into a mold, vibrate for 2 minutes, seal with plastic film after molding, and continue to cure at room temperature for up to 28 days after demolding.

[0067] Comparative Example 2

[0068] The mass proportions of raw materials prepared in Comparative Example 2 are: 297 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.2 parts of cellulose fiber, and 10 parts of anti-seepage enhancer.

[0069] In parts by weight, 20-40 parts of lithium carbonate, 15-30 parts of aluminum hydroxide with a particle size of 0.5-2 μm, 10-20 parts of aluminum silicate powder with a particle size of 200-300 μm, 5-10 parts of a powder with a particle size of 1520 nm and a specific surface area of ​​≥150 m 2 / g of nano silicon dioxide and 5-10 parts of average particle size ≤100nm, whiteness>93%, specific surface area ≥20m 2 / g of nano calcium carbonate powder is mixed and added into a ball mill, and then Al2O3 grinding balls are added according to the principle that the mass ratio of Al2O3 grinding balls to mixed powder is (10-15):1, and ball milling is carried out at a rotation speed of 300-400r / min for 2-4h, and then sifted through a 200-mesh sieve to obtain a mixed powder; the mixed powder is immersed in anhydrous ethanol, and stearic acid, methacrylic acid or aminosulfonic acid with a total mass of 3%-5% of the mass of the mixed powder is added, and the mixture is heated to 40-60°C, and then stirred at a rotation speed of 100r / min for 30-90min to obtain a coated mixed material; the coated mixed material is placed in a rotary evaporator for drying for 3-5h to obtain a coated structure polymer powder, i.e., an anti-seepage enhancer.

[0070] After obtaining the anti-seepage enhancer, add ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate, high-efficiency water reducer and anti-seepage enhancer weighed by weight into a mixer and slowly stir at a speed of 100-125r / min for 5 minutes to mix the dry materials evenly; then add water to the mixer and slowly stir at a speed of 100-125r / min for 3 minutes; then slowly add cellulose fiber into the mixer and quickly stir at a speed of 195-230r / min for 5 minutes to evenly disperse the fibers and avoid agglomeration; pour the stirred slurry into a mold, vibrate for 2 minutes, seal with a plastic film after molding, and continue to cure at room temperature for up to 28 days after demolding.

[0071] Comparative Example 3

[0072] The mass proportions of raw materials prepared in Comparative Example 3 are: 297 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.5 parts of polypropylene fiber, and 10 parts of anti-seepage enhancer.

[0073] In parts by weight, 20-40 parts of lithium carbonate, 15-30 parts of aluminum hydroxide with a particle size of 0.5-2 μm, 10-20 parts of aluminum silicate powder with a particle size of 200-300 μm, and 5-10 parts of a powder with a particle size of 1520 nm and a specific surface area of ​​≥150 m 2 / g of nano silicon dioxide and 5-10 parts of average particle size ≤100nm, whiteness>93%, specific surface area ≥20m 2 / g of nano calcium carbonate powder is mixed and added into a ball mill, and then Al2O3 grinding balls are added according to the principle that the mass ratio of Al2O3 grinding balls to mixed powder is (10-15):1, and ball milling is carried out at a rotation speed of 300-400r / min for 2-4h, and then sifted through a 200-mesh sieve to obtain a mixed powder; the mixed powder is immersed in anhydrous ethanol, and stearic acid, methacrylic acid or aminosulfonic acid with a total mass of 3%-5% of the mass of the mixed powder is added, and the mixture is heated to 40-60°C, and then stirred at a rotation speed of 100r / min for 30-90min to obtain a coated mixed material; the coated mixed material is placed in a rotary evaporator for drying for 3-5h to obtain a coated structure polymer powder, i.e., an anti-seepage enhancer.

[0074] After obtaining the anti-seepage enhancer, add ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate, high-efficiency water reducer and anti-seepage enhancer weighed by weight into a mixer and slowly stir at a speed of 100-125r / min for 5 minutes to mix the dry materials evenly; then add water to the mixer and slowly stir at a speed of 100-125r / min for 3 minutes; then slowly add polypropylene fiber into the mixer and quickly stir at a speed of 195-230r / min for 5 minutes to evenly disperse the fibers and avoid agglomeration; pour the stirred slurry into a mold, vibrate for 2 minutes, seal with a plastic film after molding, and continue to cure at room temperature for up to 28 days after demolding.

[0075] Comparative Example 4

[0076] The mass proportions of raw materials prepared in Comparative Example 4 are: 297 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.5 parts of polypropylene fiber, and 1.2 parts of cellulose fiber.

[0077] Add ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate and high-efficiency water reducing agent weighed by weight into a mixer and stir slowly at a speed of 100-125r / min for 5 minutes to mix the dry materials evenly; then add water into the mixer and stir slowly at a speed of 100-125r / min for 3 minutes; then slowly add polypropylene fiber and cellulose fiber into the mixer and stir quickly at a speed of 195-230r / min for 5 minutes to disperse the fibers evenly and avoid agglomeration; pour the stirred slurry into a mold, vibrate for 2 minutes, seal with plastic film after molding, and continue to cure at room temperature for up to 28 days after demolding.

[0078] As shown in Table 1, the shotcrete with the anti-seepage enhancer provided in Example 14 has an average compressive strength of 39.57 MPa at 7 days, an average compressive strength of 53.70 MPa at 28 days, an average tensile strength of 3.70 MPa at 7 days, and an average tensile strength of 4.54 MPa at 28 days. The early and late strengths have been significantly improved, and the 7-day compressive strength can reach 42.12 MPa, and the 28-day compressive strength can reach more than 57.86 MPa. The tensile strength is also much higher than the specification requirements, and the bonding strength with the surrounding rock reaches 3.55 MPa. It is shown that the shotcrete with the anti-seepage enhancer has the characteristics of low porosity and high density, good anti-seepage performance, good resistance to groundwater erosion of the lining, and is not conducive to the dissolution of calcium, providing a rich safety reserve for the safe operation of the tunnel.

[0079] Table 1 Mechanical indexes

[0080]

[0081] In order to verify the calcium-fixing ability of the anti-seepage enhancer in shotcrete, a verification test was set up for comparison. The verification method was as follows: the standard test block was placed in the concrete anti-seepage instrument, and the seepage fluid was collected after the test. The calcium ions of the collected seepage fluid were measured by the YD200A ion detector; the concrete anti-seepage performance test used the HS-4S digital display concrete permeameter, and the detection cycle was 120 days. The test results are shown in Table 2:

[0082] Table 2 Test results data

[0083]

[0084] As shown in Table 2, the calcium ion concentrations of Examples 1 to 4 are all lower than those of Comparative Examples 1 to 4, indicating that the anti-seepage enhancer has a good ability to prevent calcium loss in concrete, especially in Example 3. Subsequently, the amount of calcium loss decreases rapidly with the extension of time, and stabilizes at about 25 mg / L at 120 days. Therefore, as the seepage time increases, its slow-release advantage is gradually reflected, that is, the anti-seepage enhancer can not only play a good role in preventing seepage and crystallization in the early stage, but also has a better effect on preventing long-term seepage and crystallization. Long-term seepage will make more anti-seepage enhancers play a role, and achieve the purpose of resisting long-term seepage and crystallization. For water-rich tunnels, especially water-rich tunnels with corrosive groundwater, it can effectively prevent the problems of lining degradation and crystallization blockage of drainage pipes caused by the initial support shotcrete seepage, thereby ensuring the safety of the tunnel structure and the smooth operation of the drainage system.

[0085] Combined with the measurement results of the change in calcium ion concentration and the impermeability coefficient of Example 3 and Comparative Example 1, it can be seen that the impermeability enhancer will make the shotcrete more compact and the impermeability performance is much higher than that of the general shotcrete. It also reflects from the side that the shotcrete added with the impermeability enhancer has a smaller porosity, indicating that the impermeability enhancer has the function of making the concrete denser under the action of seepage, and once again verifies that the impermeability enhancer can effectively prevent the seepage crystallization problem of shotcrete in the initial support of the tunnel.

[0086] Lithium carbonate plays an important role in improving the early strength of cement. Lithium carbonate will form a large amount of calcium sulfonate in a short period of time, thereby quickly forming a spatial grid structure and improving the early compressive strength. Secondly, nano-silica can fully absorb the calcium hydroxide formed at the early stage of the cement concrete interface, especially in the early stage. The generated calcium silicate gel remains in the concrete and can be tightly consolidated with the calcium hydroxide crystals. The pores in the concrete are quickly reduced, thereby improving the density and compressive / tensile strength of the concrete. The extremely fine nano-calcium carbonate crystals have the function of nucleation sites, which can provide a large number of nucleation sites for calcium carbonate crystals in the concrete, which helps to promote the aggregation of concrete calcium carbonate crystals in the concrete to fill the pores, improve the density of the concrete, and avoid the crystals being washed away by the seepage of groundwater in the primary shotcrete.

[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0088] In summary, the anti-seepage shotcrete of the present invention applied to limestone areas, after adding polypropylene fiber, cellulose fiber and anti-seepage enhancer, has the characteristics of low porosity and high density, good anti-seepage performance, good resistance to groundwater erosion of lining, and provides a rich safety reserve for safe operation of tunnels. The present invention not only has a good seepage and crystallization prevention effect in the early stage, but the subsequent seepage process will make more anti-seepage enhancers play a role, and the shotcrete is more dense, which serves the purpose of resisting long-term seepage crystallization. For water-rich tunnels in limestone areas, especially water-rich tunnels with corrosive groundwater, it can effectively prevent the seepage crystallization problem of shotcrete in the initial support of tunnels.

Claims

1. An anti-seepage shotcrete used in limestone areas, characterized in that: The invention is composed of the following raw materials in parts by weight: 297 parts of ordinary Portland cement, 91 parts of fly ash, 68 parts of silica fume, 863 parts of fine aggregate, 765 parts of coarse aggregate, 196 parts of water, 7.3 parts of high-efficiency water reducing agent, 1.5 parts of polypropylene fiber, 1.2 parts of cellulose fiber and 10-40 parts of anti-seepage enhancer.

2. The anti-seepage shotcrete used in limestone areas according to claim 1, characterized in that: The fly ash is first-grade fly ash.

3. The anti-seepage shotcrete used in limestone areas according to claim 1, characterized in that: The fine aggregate is river sand with a particle size distribution of 0 to 2 mm.

4. The anti-seepage shotcrete used in limestone areas according to claim 1, characterized in that: The coarse aggregate is crushed stone with a particle size of 5 to 8 mm.

5. The anti-seepage shotcrete used in limestone areas according to claim 1, characterized in that: The high efficiency water reducer described is a powdered polycarboxylate water reducer.

6. The anti-seepage shotcrete used in limestone areas according to claim 1, characterized in that: The density of the polypropylene fiber is 0.91 g / cm 3 , melting point 165~175℃, ignition point 590℃, length 1224mm, diameter 2030μm, aspect ratio>500, elongation at break 23%, tensile strength>2800MPa. Breaking strength ≥300MPa, elastic modulus ≥2500MPa, Poisson's ratio 0.29~0.

46.

7. The anti-seepage shotcrete used in limestone areas according to claim 1, characterized in that: The cellulose fiber is 1.10 g / cm 3 , length 6mm, diameter 15-20μm, breaking strength ≥700MPa.

8. The anti-seepage shotcrete used in limestone areas according to claim 1, characterized in that: The anti-seepage enhancer comprises the following steps: 1) ball-milling 2040 parts of lithium carbonate, 1530 parts of aluminum hydroxide, 1020 parts of aluminum silicate powder, 5-10 parts of nano silicon dioxide and 5-10 parts of nano calcium carbonate by weight to obtain a mixed powder; 2) soaking the mixed powder in anhydrous ethanol, adding stearic acid, methacrylic acid or aminosulfonic acid, Heating to 40-60° C., and then stirring at a rotation speed of 100 r / min for 30-90 min to obtain a coated mixture; 3) Drying the coated mixed material to obtain coated structure polymer powder. In step 1), the particle size of the aluminum hydroxide is 0.5 to 2 μm; the particle size of the aluminum silicate powder is 200 to 300 μm; The particle size of the nano silicon dioxide is 1520nm and the specific surface area is ≥150m 2 / g; the average particle size of the nano calcium carbonate is ≤100nm, whiteness>93%, and specific surface area is ≥20m 2 The ball milling is specifically as follows: the raw materials are dispersed and mixed at high speed and then added into a ball mill, and then Al2O3 grinding balls are added, and the raw materials are ball milled at a speed of 300-400 r / min for 2-4 hours, and then sieved through a 200-mesh sieve to obtain a mixed powder. The total mass of stearic acid, methacrylic acid and / or aminosulfonic acid added in step 2) is 3% to 5% of the mass of the mixed powder. The drying method of step 3) is: drying in a rotary evaporator for 3 to 5 hours.

9. The method for preparing anti-seepage shotcrete for limestone areas according to any one of claims 1 to 8, characterized in that: The steps include: 1) First, add the ordinary Portland cement, fly ash, silica fume, fine aggregate, coarse aggregate, high-efficiency water reducer and anti-seepage enhancer weighed by weight into a mixer and stir slowly to mix the dry materials evenly; 2) Then add water to the blender and stir slowly; 3) Slowly add the polypropylene fiber and the cellulose fiber into the mixer and stir quickly to disperse the fibers evenly and avoid agglomeration; 4) Pour the stirred slurry into a mold, vibrate it into shape, and seal it with a plastic film. After demoulding, continue to cure it at room temperature for 28 days. The slow stirring time of step 1) is 5 minutes, the slow stirring time of step 2) is 3 minutes, the fast stirring time of step 3) is 5 minutes, and the vibration time of step 4) is 2 minutes.

10. The method for preparing anti-seepage shotcrete for limestone areas according to claim 9, characterized in that: The speed of slow stirring is 100-125r / min, and the speed of fast stirring is 195-230r / min.